Safety of Hydrocortisone Premedication Discontinuation in Patients with Inflammatory Bowel Disease on Maintenance Therapy with Infliximab: a Prospective Clinical and Pharmacological Study. (18th November 2020) - Tran-Minh, My-Linh; Gornet, Jean-Marc; Maillet, Marianne; Houze, Pascal; Simon, Marion; McLellan, Paul; Hassid, Deborah; Vivier-Chicoteau, Justine; Baudry, Clotilde; Hammoudi, Nassim; Allez, Matthieu
Abstract: Background: Hydrocortisone premedication reduces the risk of antibodies to infliximab [ATIs] formation in patients receiving infliximab [IFX] therapy for inflammatory bowel disease [IBD]. Aim: We aimed to determine the safety of hydrocortisone premedication withdrawal in IBD patients with sustained clinical response on maintenance therapy with IFX. Methods: We performed an observational prospective pharmacoclinical study in a tertiary referral centre, including all consecutive IBD outpatients with no previous IFX infusion reaction and in clinical remission on maintenance IFX [alone or in combination therapy] for at least 6 months. This cohort was followed for 1 year after discontinuation of hydrocortisone premedication. Results: Among the 268 IBD outpatients, 95 patients met the inclusion criteria [mean age 38 years; 64% male; 80% Crohn's disease; 45% combination therapy]. The median IFX duration was 5 years [0.54–14] with a mean infused dose of 533 mg [200–1000] and a mean interval duration of 7.9 weeks [4–10]. None of the patients developed permanent ATIs or infusion-related reaction at 1 year. Four patients developed transient ATIs without loss of clinical response. There was no significant variation of infliximab serum trough levels [5.5 µg/mL vs 5.9 µg/mL] measured at the time of the three IFX infusions before and after hydrocortisone withdrawal. Loss of response rate to IFX was 18% at 1 year. Conclusions: Hydrocortisone discontinuation is safe in IBD patients with sustained clinical remission on maintenance therapy with IFX. Our data suggest that routine premedication with hydrocortisone is unnecessary in patients in prolonged remission under IFX maintenance therapy.